PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR PESERTA DIDIK DALAM MATA PELAJARAN DASAR LISTRIK ELEKTRONIKA - Halimatu Ulfah Halimatu Ulfah; Ariep Jaenul Ariep Jaenul; Agung Pangestu Agung Pangestu; Dian Nugraha Dian Nugraha (Indra institute Research & Publication, 2021)
Assessment of learning outcomes essentially aims to measure the success of learning carried out by the teacher as well as to measure the success of students in mastering predetermined competencies. Learning outcomes can be said to be successful if most of the students' scores get scores on the KKM. At the time of observation in the Basic Electrical Electronics subject, it was found that around 19 students got scores that were still below the KKM during midterm tests. This study aims to obtain information related to an increase in learning outcomes in Basic Electrical Electronics in the competence of explaining and using electronic measuring instruments. This study used an experimental research method with a one-group model and used the pre-test and post-test methods as a means of comparison testing with a population of 10th grade students at one of the private vocational schools majoring in Industrial Electronic Engineering in the Bekasi area and a sample of 34 class 10 students majoring in Industrial Electronics Engineering. The results of the study can be concluded that there is a positive influence on the inquiry learning model on student learning outcomes in the Basic Electrical Electronics subject and dk = 33 is 2.445.